Individualized monitoring of nuclear factor of activated T cells-regulated gene expression in FK506-treated kidney transplant recipients - Sommerer, Claudia; Zeier, Martin; Meuer, Stefan; Giese, Thomas (Transplantation, 2010)
Background. - The suggested key mechanism of both cyclosporine A (CsA) and FK506 is the inhibition of calcineurin phosphatase activity, preventing nuclear factor of activated T cells (NFAT)-translocation into the nucleus of T cells, with a subsequent transcriptional block of crucial cytokine genes. However, the two drugs exert different clinical activities as exemplified by the ability of FK506 to treat acute rejections. Inhibition of calcineurin activity by FK506 occurs in vitro at the same or even higher dose as for CsA; however, the magnitude of clinical and experimental immunosuppression is higher, indicating that FK506 may act in a calcineurin-independent way. - Methods. - To test this hypothesis, we measured the inhibition of NFAT-regulated gene expression in 262 stable kidney transplanted patients after FK506 intake. - Results. - Previously, we showed that the optimal degree of NFAT inhibition in patients treated with CsA is between 15% and 30% residual gene expression. A considerable number of patients treated with FK506 do not achieve this level of immunosuppression despite therapeutic drug concentrations. Importantly, FK506 does inhibit protein translation. This insufficient degree of NFAT inhibition was associated with a higher rate of biopsy-proven acute rejection but also with a lower incidence of recurrent infections. Conversion of CsA to FK506 causes immediately reduced inhibition of NFAT-regulated gene expression. - Conclusion. - We could demonstrate that a considerable number of FK506-treated patients benefit from the drug, irrespective of the potency of NFAT inhibition in T cells by a yet unknown mechanism. Nevertheless, residual expression of NFAT-regulated genes seems to be a useful pharmacodynamic method to monitor FK506 therapy in renal transplant patients.
Gesehen am 14.09.2023